I am the messenger - Zusak, Markus (Knopf, 2005)
After capturing a bank robber, nineteen-year-old cab driver Ed Kennedy begins receiving mysterious messages that direct him to addresses where people need help, and he begins getting over his lifelong feeling of worthlessness.